In silico Studies for Tridax procumbens Linn Phyto constituents with Anti-inflammatory Receptors - Swathy, Bekkeri (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: A wound is categorized as a breakdown or opening of the skin, which could lead to malfunctioning of the skin. Materials and Methods: Interleukin-1 receptor-associated kinases are key components in the signal transduction pathways utilized by interleukin-1 receptor and interleukin-18 receptor. Results and Discussion: The critical role of IRAK-4 in inflammatory processes, and modulation of IRAK-4 kinase activity presents an attractive therapeutic approach for the treatment of inflammatory diseases. To identify the potent IRAK-4 inhibitors with new anti-inflammatory therapeutic agents from selected herbal plants and their extract with the help of in-silico data. Conclusion: In the present study, we have investigated in silico computational studies for Tridax procumbens phytoconstituents against the molecular targets involved in the anti-inflammatory process. The molecular docking interactions show good binding affinity against the molecular targets of the anti-inflammatory target, namely, ILAK4. Among the ligands docked against ILAK4, Nodakenin (14), and Apigenin 7-O-β-D-glucoside (16) showed excellent free energy binding with dock score values of −9.4 and −10 kcal/mol, respectively. These results suggest that further mechanistic studies are to be done for these phytoconstituents against anti-inflammation.